Designing a segmented, indexed data warehouse and performance analysis and improvement of association rules mining with the apriori algorithm on a virtual supermarket database - Mahmud, Shahtab (BRAC University, 2013)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2005.